Intestinal Health of Pigs Upon Weaning: Challenges and Nutritional Intervention - Zheng, Lan; Duarte, Marcos Elias; Sevarolli Loftus, Ana; Kim, Sung Woo (Frontiers in Veterinary Science, 2021)
The primary goal of nursery pig management is making a smooth weaning transition to minimize weaning associated depressed growth and diseases. Weaning causes morphological and functional changes of the small intestine of pigs, where most of the nutrients are being digested and absorbed. While various stressors induce post-weaning growth depression, the abrupt change from milk to solid feed is one of the most apparent challenges to pigs. Feeding functional feed additives may be viable solutions to promote the growth of nursery pigs by enhancing nutrient digestion, intestinal morphology, immune status, and by restoring intestinal balance. The aim of this review was to provide available scientific information on the roles of functional feed additives in enhancing intestinal health and growth during nursery phase. Among many potential functional feed additives, the palatability of the ingredient and the optimum supplemental level are varied, and these should be considered when applying into nursery pig diets. Considering different stressors pigs deal with in the post-weaning period, research on nutritional intervention using a single feed additive or a combination of different additives that can enhance feed intake, increase weight gain, and reduce mortality and morbidity are needed to provide viable solutions for pig producers. Further research in relation to the feed palatability, supplemental level, as well as interactions between different ingredients are needed.